"Missing mutations" in MPS I: Identification of two novel copy number variations by an IDUA‐specific in house MLPA assay. Issue 9 (18th July 2019) - Jahic, Amir; Günther, Sven; Muschol, Nicole; Fossøy Stadheim, Barbro; Braaten, Øivind; Kjensli Hyldebrandt, Hanne; Kuiper, Gé‐Ann; Tylee, Karen; Wijburg, Frits A.; Beetz, Christian
Abstract: Background: Mucopolysaccharidosis type I (MPS I) is a rare, recessively inherited lysosomal storage disorder, characterized by progressive multi‐systemic disease. It is caused by a reduced or absent alpha‐l iduronidase (IDUA) enzyme activity secondary to biallelic loss‐of‐function variants in the IDUA . Over 200 causative variants in IDUA have been identified. Nevertheless, there is a fraction of MPS I patients with only a single mutated IDUA allele detectable. Methods: As genetic testing of MPS I is usually based on sequencing methods, copy number variations (CNVs) in IDUA can be missed and therefore presumably remain underdiagnosed. The aim of this study was the detection of CNVs using an IDUA ‐specific in house multiplex ligation‐dependent probe amplification (MLPA) assay. Results: A total of five unrelated MPS I patient samples were re‐analyzed after only a single heterozygous IDUA mutation c.979G>C (p.A327P), c.1469T>C (p.L490P), c.1598C>G (p.P533R), c.1205G>A (p.W402X), c.973‐7C>G (p.?) could be identified. We detected a novel splice site variant c.973‐7C>G (p.?), as well as two novel CNVs, a large deletion of IDUA exon 14 and 3'UTR c.(1828 + 1_1829‐1)_(*1963_?)del, and a large duplication extending from IDUA exon 2 to intron 12 c.(157 + 1_158‐1)_(1727 + 1_1728‐1)dup. Conclusion: Together with the CNVs we previously identified, a total of four pathogenic IDUA CNVs have now been reported. Abstract : Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disorder caused by biallelic loss‐of‐function variants in the IDUA . However, there is a fraction of MPS I patients with only a single mutated IDUA allele detectable. We hypothesized that IDUA copy number variants (CNVs), which are not detectable by the standard diagnostic approaches, are present in some initially unresolved MPS I cases. For the detection of the CNVs we developed an IDUA ‐specific multiplex ligation‐dependent probe amplification (MLPA) Assay. In the frame of analyses we detected two novel CNVs in IDUA .